Penerapan pendekatan kontekstual dalam pembelajaran Matematika untuk meningkatkan pemahaman konsep perkalian pada siswa kelas III SD Negeri 27 Talang Kelapa - M. Abda Rafli; Lusiana; Aan Suriadi (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study began with the problem of low understanding of the concept of multiplication in grade III students of SD Negeri 27 Talang Kelapa, which tends to be based only on memorization without understanding the meaning of multiplication in depth. The purpose of this study was to determine how to improve the understanding of the concept of multiplication through the application of a contextual approach in mathematics learning. The method used in this study is a quantitative descriptive method with data collection techniques in the form of tests, namely pretest and posttest. The subjects of this study were 28 grade III students of SD Negeri 27 Talang Kelapa. The pretest results showed an average value of 49.96, while the posttest results increased to 87.78. The analysis of this data using the N-Gain formula obtained a score of 0.75. The results of this data analysis indicate that after implementing learning using a contextual approach, an increase in the concept of multiplication was found with a high category.